Analysis of the Tourism Village-Based Tourism Potential in Supporting Tourism Development In Cirebon Regency - Sudiana Wachyudi; Annisaa Eka Warliati; Giatri Giatri (Ann Publisher, 2025)
Background. The tourism sector is a potential sector that can be developed as one of the sources of regional income. To increase regional original income, the development and utilization program of regional tourism resources and potential is expected to contribute to economic development. Purpose. The development of tourism villages is not only aimed at diversifying tourism products, but also becomes a strategic instrument for economic equity, job creation, and local community empowerment. Method. The research method used is a qualitative descriptive method with data collection techniques through observation, in-depth interviews and documentation studies. The analysis was carried out by examining the potential tourist attractions, accessibility, amenities, and the role of local communities in the management of tourist villages. Results. The results of the study show that Cirebon Regency has considerable potential for Tourism Villages, especially in aspects of culture, traditional culinary and rural people's lives. Therefore, tourism villages can be one of the strategies to develop tourism in Cirebon Regency. However, the development of Tourism Villages still faces a number of obstacles, such as the limitation of professional human resources, lack of optimal promotion, and uneven support for tourism infrastructure. Conclusion. This study concludes that Tourism Villages have the potential to be a driver of regional tourism development if managed in an integrated manner by involving the government, the community and tourism business actors. Implementation. This research recommendation is expected to be considered in the formulation of tourism development policies in Cirebon Regency.